Dari buku ke buku : sambung menyambung menjadi satu - Swantoro, P. (Jakarta : Kepustakaan Populer Gramedia bekerjasama dengan Rumah Budaya TeMBI, 2002)
Historical review of some important events in Indonesia published in some old books in the Dutch colonial period.
Includes bibliographical references (p. [404]-416) and index.
Keywords: History -- Research -- Indonesia; Indonesia -- History -- 1798-1942